INTEGRATION OF D IGITAL TOOLS IN TEACHER EDUCATION AND THEIR IMPACT ON LEARNING OUTCOMES - Dadajonova Muxtasarxon Farxod qizi,; Fakhriddin Urinboevich Toshboltaev, (Ustozlar uchun, 2025)
The incorporation of digital tools into teacher education has become increasingly pertinent as educational institutions strive to meet the demands of 21st-century pedagogy. This study examines how digital technologies are incorporated into teacher training programs and their implications on pedagogical skills and classroom efficacy. Employing a mixed-methods research design that includes surveys and observational research, this paper underscores the advantages of digital tools in enhancing instructional methodologies and learner involvement. The findings indicate notable advancements in teacher competencies, yet challenges such as technological accessibility, variability in digital literacy, and institutional resistance persist. The study concludes with strategic recommendations for enhancing digital tool adoption in teacher education.